Faith that Leads to Action: Perspectives from the Acts of the Apostles - C. Sunil Ranjar (Fakultas Teologi, Universitas Sanata Dharma, 2024)
I have been asked to speak on the theme of the conference, Faith in Action: Theology for the Changing World, from a biblical perspective, in particular from the perspective of the Acts of the Apostles. While it is true that the book of Acts does offer a cogent theological framework for a dynamic Church and world, its preceding volume, the Gospel of Luke, cannot be ignored altogether, since both Luke and Acts form a unified whole. Therefore, for this presentation it is opportune to start with the Acts of the Apostles and then go back to the Gospel of Luke.